THE EFFECT OF CHANGE MANAGEMENT, KAP SIZE, PUBLIC OWNERSHIP, AND FINANCIAL DISTRESS ON AUDITOR SWITCHING (Case Study On Mining Companies Listed On The Indonesia Stock Exchange Period 2015-2019) - Klarasati, Titi; Inayati, Nur Isna; Hariyanto, Eko; Setyadi, Edi Joko (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research aimed to analyze the effect of management change, KAP size, public ownership, and financial distress on auditor switching. This research is a quantitative study with secondary data in the form of company annual financial reports. In this study, auditor switching is calculated using dummy variables. The sample used in this study were mining companies listed on the Indonesia Stock Exchange in 2015-2019. Sampling was done by non-probability method with purposive sampling technique and obtained samples of 32 companies with 160 annual report data as observation material. The data analysis method used in this research is logistic regression analysis. The results of this study indicated that KAP size has a positive effect on auditor switching, while management change, public ownership, and financial distress have no effect on auditor switching. Keywords: Management Change, KAP Size, Public Ownership, Financial Distress, Auditor Switching.